Rêver le paysage, se soucier du vivant : pour une recherche-fiction - Gilles Clément (Projets de Paysage)
The article proposes elements to analyze, even to invent, what could be a research on landscape. It is based on texts written in similar context to the one which lead to this seminar. After having explained the context, in which the question of research is raised à the ENSP, a school where the project is taught à the article emphasises the trans-disciplinarity that landscape requires in order to be explained, understood and revealed with all its potentialities. It is deduced that the research can only be here « fiction» and be along with the dream. Then, a text explaining the project pedagogy through the dream and the importance, for the research, of the final personal study project (TPFE) conducted by the students is explored. In a third part, several difficulties and inherent principles to research are pointed out. The dream of landscape does not really fit with the protocol of landscape thesis committees. The question of archives and its compilation does not seem to be adapted to the need, in the project process, to welcome the landscape and more precisely the living. The importance given to the facts does not seem to correspond to the attention given to the dream. However, it could be possible, by emphasizing the innovation and the invention, as do certain academic professionals, to develop an alternative, corresponding to a school of project, which by nature, questions what does not exist yet, even creates it. Here, the article refers to a second text, more ancient. Without denying what has been thought, the article tries to defend the importance of the hypothesis and the experimentation, which are at the origin of every landscape project and of every research in landscape. To conclude, the articles comes back to the present, to the importance of the TPFE, as potential source of thesis subject, by quoting, among others, two projects which question the subversive role of art in landscape and the federative place of water in urban landscape.